2006
DOI: 10.2989/16085900609490387
|View full text |Cite
|
Sign up to set email alerts
|

Zambian male adolescents' perceptions about premarital sexual relationships

Abstract: The role adolescent boys play in premarital sexual activities, gender power relations, and the reproductive health risks they are exposed to, has received little attention in research. This qualitative study has aimed to explore Zambian male adolescents' perceptions and expectations about premarital sexual relationships. Seven focus group discussions were conducted between November 2000 and May 2001, in George and Chimwemwe compounds, with 53 boys aged 15 to 19. The findings reveal that adolescent premarital s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This was also attributed to poverty and the desire to meet basic needs. In Zambia, it was reported that girls were willing to engage in sex as long as the boys gave the assurance of providing money, gift or reward in advance, as a strategy for survival but the practice was not regarded as prostitution (45). Also, female students in South Africa engaged in transactional sex (sometimes abusive) due to poverty, with the expectation that material benefits (money, food etc.)…”
Section: Discussionmentioning
confidence: 99%
“…This was also attributed to poverty and the desire to meet basic needs. In Zambia, it was reported that girls were willing to engage in sex as long as the boys gave the assurance of providing money, gift or reward in advance, as a strategy for survival but the practice was not regarded as prostitution (45). Also, female students in South Africa engaged in transactional sex (sometimes abusive) due to poverty, with the expectation that material benefits (money, food etc.)…”
Section: Discussionmentioning
confidence: 99%